2014
DOI: 10.1007/s10563-014-9165-z
|View full text |Cite
|
Sign up to set email alerts
|

Semiconductor Photocatalysts for Non-oxidative Coupling, Dry Reforming and Steam Reforming of Methane

Abstract: Methane is one of the promising alternatives of petroleum, which should be used for not only a fuel but also a resource for hydrogen and more useful chemicals as with the petroleum. However, the selective methane conversion to them is still difficult in contrast to the combustion. Three types of photocatalytic reactions for methane conversion, i.e., the photocatalytic non-oxidative coupling of methane (PNOCM: 2CH4 → C2H6 + H2), the photocatalytic dry reforming of methane (PDRM: CH4 + CO2 → 2CO + 2H2) and the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 39 publications
(61 reference statements)
0
43
1
Order By: Relevance
“…They are mostly generated when inappropriate ratio of CH 4 :CO 2 is employed at elevated temperatures exceeding 800°C [32,33]. Linearly, the total amount of deposited coke has shown consistency with the overall decay in catalyst activity [34,35]. Surface deposits are difficult to be removed from the metallic catalyst surfaces (especially because of the formation of carbides in some instances) during regeneration [35,36].…”
Section: Nature Of Coke Depositsmentioning
confidence: 99%
See 1 more Smart Citation
“…They are mostly generated when inappropriate ratio of CH 4 :CO 2 is employed at elevated temperatures exceeding 800°C [32,33]. Linearly, the total amount of deposited coke has shown consistency with the overall decay in catalyst activity [34,35]. Surface deposits are difficult to be removed from the metallic catalyst surfaces (especially because of the formation of carbides in some instances) during regeneration [35,36].…”
Section: Nature Of Coke Depositsmentioning
confidence: 99%
“…Linearly, the total amount of deposited coke has shown consistency with the overall decay in catalyst activity [34,35]. Surface deposits are difficult to be removed from the metallic catalyst surfaces (especially because of the formation of carbides in some instances) during regeneration [35,36]. They exhibited slow burning rates and therefore render catalyst regeneration tedious.…”
Section: Nature Of Coke Depositsmentioning
confidence: 99%
“…Thus, heterogeneous photocatalysts for water splitting, especially for water vapor splitting, require ac ocatalyst that is catalytically inactive for the reverser eaction. Pt is ar epresentative andh ighly active cocatalyst for many photocatalytic reactions, including hydrogen production from methane and water [8][9][10][11][12] and various organic reactions involving hydrogen formation, [13][14][15][16][17][18][19] and the properties of the Pt cocatalyst can vary with the loading method andt he resulting chemical state. [7,20] Thus, if it becomes inactive for the reverser eaction, Pt may be an excellent cocatalyst.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, photocatalysis was exploited to break this thermodynamic limitation and to solve the issue of large energy requirement . Shimura and Yoshida explored Ga 2 O 3 as a photocatalyst for CH 4 and CO 2 at lower temperature . They found that, under UV irradiation, DRM could not occur at temperature below 200°C.…”
Section: Photocatalytic Conversion Of Ch4 and Co2mentioning
confidence: 99%
“…,[286][287][288][289][290][291][292] Shimura and Yoshida explored Ga 2 O 3 as a photocatalyst for CH4 and CO 2 at lower temperature 289. They found that, under UV irradiation, DRM could not occur at temperature below 200°C.…”
mentioning
confidence: 99%